Strontium‐Doped Hydroxyapatite Promotes Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells in Osteoporotic Rats through the CaSR‐JAK2/STAT3 Signaling Pathway. Issue 9 (14th July 2022) - Ren, Wen-Hao; Xin, Shanshan; Yang, Kai; Yu, Yan-Bin; Li, Shao-Ming; Zheng, Jing-Jing; Huang, Kai; Zeng, Rong-Chang; Yang, Xiao-Xia; Gao, Ling; Li, Shuo-Qi; Zhi, Keqian
Abstract : Self‐repair of critical bone defects from periodontitis, tumor resection, and trauma is difficult. Osteoporosis is an abnormal bone metabolism disease characterized by increased bone resorption, decreased bone formation, and decreased activity of bone marrow mesenchymal stem cells (BMSCs), which further inhibits the repair of bone defects. Improving the osteogenic ability of BMSCs after osteoporosis is an important step in treating osteoporotic bone defects. Hydroxyapatite (HA) with good biocompatibility is widely used in bone material research. HA and strontium‐doped hydroxyapatite (Sr‐HA) microspheres are synthesized following a hydrothermal method, and the characteristics and the ability of these microspheres are explored to promote osteogenesis. Further, the role of the calcium‐sensing receptor (CaSR) and Janus kinase 2 gene/signal transducers and activators of transcription 3 (JAK2/STAT3) signaling pathway in this process are investigated. The results show that Sr‐HA, rather than HA alone, significantly promote the osteogenic differentiation of BMSCs in vitro and bone formation in vivo. Further, the effect of promoting osteogenic differentiation is realized by activating the CaSR‐JAK2/STAT3 signaling pathway. Therefore, the study demonstrates that Sr‐HA is the better choice for restoring critical bone defects. Abstract : The quantity and quality of bone marrow mesenchymal stem cells (BMSCs) play an important role in repairing osteoporotic bone defects. Herein, it is demonstrated that Sr20‐HA promotes osteogenic differentiation by activating calcium‐sensing receptor (CaSR) receptor and promoting the expression of p‐JAK2 and p‐STAT3. This study shows that Sr20‐HA is the better choice for restoring critical bone defects in osteoporosis.